Migration and Conflict in a Global Warming Era A Political Understanding of Climate Change - Klepp, Silja; Fröhlich, Christiane (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue explores underrepresented aspects of the political dimensions of global warming. It includes post- and decolonial perspectives on climate-related migration and conflict, intersectional approaches, and climate change politics as a new tool of governance. Its aim is to shed light on the social phenomena associated with anthropogenic climate change, as well as its multidimensional and far-reaching political effects, including climate-induced migration movements and climate-related conflicts in different parts of the world. In doing so, it critically engages with securitizing discourses and the resulting anti-migration arguments and policies in the Global North in order to identify and give a voice to alternative and hitherto underrepresented research and policy perspectives. In this way, it aims to contribute to a fact-based, critical, and holistic approach to human mobility and conflict in the context of political and environmental crisis.